Pengaruh Substitusi Daun Stevia (Stevia Rebaudiana) Sebagai Pemanis Alami Terhadap Daya Rapuh Dan Daya Terima Biskuit Ubi Jalar Ungu (Ipomoea batatas L.) - Astuti, Fitri Ayu, Endang Nur Widiyaningsih, SST, M.Si Med, Fitriana Mustikaningrum, S. Gz., M. Sc (2017)
DEPARTEMEN OF NUTRITION SCIENCE FACULTY OF HEALTH SCIENCE UNIVERSITAS MUHAMMADIYAH SURAKARTA BACHELOR THESIS ABSTRACT EFFECT OF SUBSTITUTION STEVIA (Stevia rebaudiana) AS OF NATURAL RESOURCES SWEETENERS ON FRAGILITY AND ACCEPTABILITY OF PURPLE SWEET POTATO (ipomoea batatas L.) BISCUITS Introduction: Excessive sugar consumption can cause adverse health effects, such as diabetes mellitus, obesity and tooth decay. Sugar can be replaced with other natural sweeteners such as stevia leaves (Stevia rebaudiana). Granulated sugar plays an important role in determining the quality of biscuits. Sensory quality are known to test the acceptability but not yet able to provide accurate data. Measurements of textures by using tools such fargility tests are considered more accurate. Purpose: To measure the influence of substitution leaves of Stevia (Stevia rebaudiana) as a natural sweetener to the fragility and acceptability of purple sweet potato (Ipomoea batatas L.) biscuits. Methods: The study design used was completely randomized design (CRD) with 4 treatments, 0 g, 1,351 g, 2,702 g and 4.053 g of powdered stevia leaf. Fragility and acceptability of purple sweet potato biscuits were analyzed using one way anova statistical test and if there is a difference followed by DMRT. Results: The results showed that there is a substitution effect of stevia leaf powder to the fragilityof purple sweet potato biscuits with a significance of p = 0.007. Highest levels of hardness shown by biscuit with substitution of 1.351 g. There is a substitution effect of stevia leaf powder to the acceptance of color, flavor, taste and overall with significant value respectively p = 0.02; p = 0.02; p = 0.00; and p = 0.04. There is no substitution effect of stevia leaf powder to the test of acceptability texture of a biscuit with a value of significance p = 0.28. Conclusion: Based on the research that has been done, it is recommended to use stevia leaf powder amounted of 1,352 g and 45 g of sugar. Keywords: Stevia leaf powder, purple sweet potato flour, fragility, acceptability, biscuits.